Relation Between Perinatal Depressive Symptoms, Harm Avoidance, and a History of Major Depressive Disorder: A Cohort Study of Pregnant Women in Japan - Kubota, Chika; Inada, Toshiya; Shiino, Tomoko; Ando, Masahiko; Aleksic, Branko; Yamauchi, Aya; Sato, Maya; Ohara, Masako; Murase, Satomi; Morikawa, Mako; Nakamura, Yukako; Okada, Takashi; et al. (Frontiers in Psychiatry, 2019)
Abstract Introduction: The relationship between perinatal depressive symptoms, harm avoidance (HA), and a history of major depressive disorder (MDD) was examined in a prospective cohort study. Methods: This study was conducted from May 1, 2011 to December 31, 2016. A history of MDD was evaluated using the Inventory to Diagnose Depression, Lifetime version during pregnancy. Depressive state and HA were evaluated in early pregnancy and at 1 month postnatal using the Edinburgh Postnatal Depression Scale (EPDS) and Temperament and Character Inventory, respectively. The relationship between these variances was examined using structural equation modeling. Results: A total of 338 participants with complete data were included in the present study. Pregnant women with compared with those without a history of MDD were observed to have a significantly higher intensity of HA and more severe depressive symptoms in both the prenatal and postnatal periods. A history of MDD affected the severity of depressive symptoms (standardized path coefficient [SPC]=0.25, p<0.001) and the intensity of HA during pregnancy (SPC=0.36, p<0.001). The intensity of HA during pregnancy affected that at 1 month postnatal (SPC=0.78, p<0.001), while the severity of depressive symptoms as assessed by the EPDS during pregnancy affected that at 1 month postnatal (SPC=0.41, p<0.001). The SPC for perinatal HA to postnatal depressive symptoms (SPC=0.13, p=0.014) was significant and higher than that for perinatal depressive symptoms to postnatal HA (SPC=0.06, p=0.087). Conclusion: The present results suggest that early intervention in pregnant women with a history of MDD or a high intensity of HA is important to prevent postnatal depressive symptoms.